Chapter 2 Barents Sea oil and gas 2025 Three scenarios - Zolotukhin, Anatoly (Taylor & Francis, 2015)
What are some of the possible futures for Barents Sea oil and gas? This chapter draws upon the key trends and issues covered by the book's thematic chapters and presents three scenarios on the prospects for Norwegian-Russian cooperation in the Barents Sea. Ultimately human interaction will play a large part in how the Barents Sea is developed, and we have therefore given the scenarios metaphorical titles related to interaction between people.